High-Density Lipoprotein – A Hero, a Mirage, or a Witness? - Sviridov, Dmitri (Frontiers in Cardiovascular Medicine, 2014)
Negative relationship between plasma High Density Lipoprotein (HDL) levels and risk of cardiovascular disease is a firmly established medical fact, but attempts to reproduce protective properties of HDL by pharmacologically elevating HDL levels were mostly unsuccessful. This conundrum presents a fundamental question: were the approaches used to raise HDL flawed or the protective effects of HDL are an epiphenomenon. Recent attempts to elevate plasma HDL were universally based on reducing HDL catabolism by blocking reverse cholesterol transport. Here we argue that this mode of HDL elevation may be mechanistically different to natural mechanisms and thus be counterproductive. We further argue that independently of whether HDL is a driving force or a surrogate measure of the rate of reverse cholesterol transport, approaches aimed at increasing HDL supply, rather than reducing its catabolism, would be most beneficial for speeding up reverse cholesterol transport and improving protection against cardiovascular disease.